Pengaruh Budaya Organisasi, Keterlibatan Kerja dan Employee Engagement terhadap Kinerja Karyawan pada PDAM Tirta Kerta Raharja Kabupaten Tangerang - Adam Saputra Ramadhan; Maswanto Maswanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of organizational culture, work involvement, and employee engagement on employee performance in the Tirta Kerta Raharja Regional Drinking Water Company, Tangerang Regency. This study uses a quantitative approach with a survey method. The number of samples used was 84 employees who were selected through certain sampling techniques. Data collection was carried out by distributing questionnaires online through Google Form. The data obtained was then analyzed using multiple linear regression analysis with the help of SPSS software version 20. The results of the study show that organizational culture has a positive and significant influence on employee performance. Work engagement also has a positive and significant impact on performance. In addition, employee engagement shows a positive and significant influence in improving employee performance. Based on the results of the F test, organizational culture, work engagement, and employee engagement simultaneously significantly affect employee performance. This is shown by a Fcal value of 89.183 which is greater than Ftabel of 2.719 and a significance value of 0.000 which is smaller than 0.05. As such, companies need to strengthen organizational cultures that support productivity, increase employee engagement through active participation, and create a work environment that supports employee engagement. These three factors have been empirically proven to have an important role in improving the performance of human resources. Improving these aspects can have a positive impact on work effectiveness and the achievement of overall organizational goals. In addition, the company's management is expected to continue to conduct periodic evaluations of the conditions of work culture and employee involvement. Implementing HR management strategies that are responsive to employee needs is also very important in maintaining long-term motivation and commitment.